2012
DOI: 10.1007/s00467-012-2283-9
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab therapy in a child with hemolytic uremic syndrome and CFI mutation

Abstract: It is our belief that eculizumab can be the treatment of choice in children who have plasma exchange-refractory HUS with defective regulation of the alternative complement pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 14 publications
1
13
0
2
Order By: Relevance
“…[8][9][10] The resulting lack of inhibition leads to uncontrolled complement activation, TMA, endothelial lesions, and platelet aggregation leading to the typical triad of HUS symptoms: hemolytic anemia, thrombocytopenia, and renal insufficiency. 5 Distinguishing aHUS from STEC-HUS, particularly in infants, is often difficult and may take several days, which may be detrimental to outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] The resulting lack of inhibition leads to uncontrolled complement activation, TMA, endothelial lesions, and platelet aggregation leading to the typical triad of HUS symptoms: hemolytic anemia, thrombocytopenia, and renal insufficiency. 5 Distinguishing aHUS from STEC-HUS, particularly in infants, is often difficult and may take several days, which may be detrimental to outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies have also been published in older children, revealing the benefits of eculizumab after unsuccessful PE/PI. 8,[15][16][17][18] Because our patient had a very high probability of aHUS, even without having results of genetic testing, and given these positive reports of eculizumab, we decided to use eculizumab as first-line therapy without previous plasmapheresis. Our decision was also encouraged by the need to initiate treatment quickly to avoid TMA progression and permanent organ damage, because other studies have shown a negative effect of treatment delay to recovery of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Three CFI variants seen in our study have previously been reported in acute hemolytic-uremic syndrome (aHUS) and 2 ADAMTS13 variants were reported in TTP; 1 CFHR5 variant is known to cause CFH-related protein deficiency. [21][22][23][24][25] A CFD variant (c.357116C.A) was detected only in African American patients with TMA. The median number of gene variants seen in transplant recipients with TMA was 1 (range, 0-7) and 0 (range, 0-2) in those without TMA (P , .0001).…”
Section: Gene Variants Identifiedmentioning
confidence: 99%
“…Özellikle uluslarası konsensüs raporlarında, a HÜS hastalarında eculizumab kullanımı tedavinin erken basamaklarında önerilmektedir. Bununla beraber, bazı yazarlar, eculizumab plazma tedavilerine yanıt-sız olan aHÜS'lü olgularda önerilmiştir (2,12,13) . Bu öneriler güçlü çocuk tabanlı klinik araştırmalara dayanmasa da, genelde ergen ve yetişkinlerdeki olgu sunumlarına dayanmaktadır (8) .…”
Section: Discussionunclassified
“…Klinik hastalar; coombs negatif mikroanjiopatik hemolitik anemi, trombositopeni ve böbrek yetmezliği tablosu ile başvururlar (1)(2)(3) . Çocuklarda atipik HÜS (aHÜS), %10 sıklıkta görülür (1) .…”
Section: Introductionunclassified